HbE Variants: An Experience from Tertiary Care Centre of Eastern India - Mukherjee, Sriranjan; Das, Mou; Basu, Keya; Sengupta, Moumita; Karmakar, Subhrajyoyi; Jha, Ashish Kumar; Bandopadhyay, Manimoy (Annals of Pathology and Laboratory Medicine, 2020)
Background- HbE is the second most common structural haemoglobin disorder after sickle cell haemoglobin (HbS). Haemoglobin E (HbE) is variant haemoglobin with a mutation in the globin gene causing substitution of glutamic acid for lysine at position 26 of the globin chain. Aims & Objectives- 1) To Know demographical parameters of HbE variants and 2) To know the Hematological parameters of HbE variants. Materials & Methods- The present single-centre, retrospective, cross-sectional study was carried out on consecutive 2035 Hb-E variants who were screened by CE-HPLC for hemoglobinopathies in the Thalassemia control unit (TCU) in our tertiary care referral centre after obtaining the proper approval from ethical committee of the institution and informed consent from the patients. The evaluation was done in Bio-Rad Variant Haemoglobin Testing System (Hercules, California, USA) using variant b-thalassemia short program pack. All the analyses were done using IBM SPSS statistics software, version 19 and MedCalc software, version 12.3.0.0. Result- Among 2035 subjectsâ€™ majority (80%) were diagnosed as HbE carrier. Age ranged from 1 year to 75 years with mean of 19.1Â±13.2 years. Study population mostly comprised of antenatal mothers (23.2 %) followed by premarital (20.2%), children (18.1 %), post marital (17.4%), %), family member of affected person (16.6%), suspected patient (3.5 %) family member of carrier (0.2%) and others (0.8%). Conclusion: HbE disorders are paradox: its behaviour ranges from good, bad to ugly and the value of HbE does not correlate with the severity of the diseases.